An A‐D‐A′‐D‐A Conjugated Molecule Entailing Diazapentalene Unit for an n‐Type Organic Semiconductor. Issue 10 (14th January 2019) - Lin, Gaobo; Wang, Lingna; Yang, Yizhou; Liu, Zitong; Zhang, Guanxin; Zhang, Deqing
Abstract: Conjugated molecules with low lying LUMO levels are demanding for the development of air stable n‐type organic semiconductors. In this paper, we report a new A‐D‐A′‐D‐A conjugated molecule (DAPDCV ) entailing diazapentalene (DAP) and dicyanovinylene groups as electron accepting units. Both theoretical and electrochemical studies manifest that the incorporation of DAP unit in the conjugated molecule can effectively lower the LUMO energy level. Accordingly, thin film ofDAPDCV shows n‐type semiconducting behavior with electron mobility up to 0.16 cm 2 ⋅V −1 ⋅s −1 after thermal annealing under N2 atmosphere. Moreover, thin film ofDAPDCV also shows stable n‐type transporting property in air with mobility reaching 0.078 cm 2 ⋅V −1 ⋅s −1 . Abstract : TA‐DAA ! An A‐D‐A′‐D‐A conjugated molecule containing dicyanovinylene groups and a diazapentalene core was synthesized, and investigated as an n‐type semiconductor with electron mobility up to 0.16 cm 2  V −1  s −1 .